Molecular imaging and immunotherapy in atherosclerotic cardiovascular disease - Ståhle, Mia (fi=Turun yliopisto|en=University of Turku|, 2020)
Atherosclerotic cardiovascular disease (ASCVD) is a disorder that affects both heart and blood vessels. It is caused by atherosclerosis, a chronic, low-grade inflammatory disease, which is characterized by the accumulation of lipids in the arterial wall. Modified lipoproteins contain pro-inflammatory epitopes, such as phosphorylcholine (PC), that interact with inflammatory cells in the vascular wall, thereby accelerating the development of atherosclerotic lesions. The main cause of myocardial infarction (MI) arises from a rupture of an unstable, inflamed atherosclerotic lesion in the coronary artery. The MI induces an intense inflammatory response that is essential for myocardial repair and scar formation, but which is also implicated in the onset of heart failure over time. Molecular imaging techniques can be potentially used for identification of new molecular targets, such as glucagon-like peptide-1 receptor (GLP-1R), that are involved in inflammatory and repair processes. The aim of this thesis was to investigate whether a novel immunotherapy targeting the PC epitope improves vascular function and attenuates atherosclerotic inflammation in mice. A positron emission tomography (PET) tracer 68Ga¬NODAGA-exendin-4 was evaluated for detection and imaging of GLP-1R expression after MI and in atherosclerosis in experimental models. In vivo PET imaging, ultrasound imaging, tissue autoradiography, immunohistological stainings, and cell assays were utilized as the main methods in the studies. This thesis showed that treatment with the PC immunotherapy preserved coronary artery function and attenuated the uptake of an established inflammation tracer, glucose analog 18F-FDG, in atherosclerotic lesions in mice. 68Ga-NODAGA¬exendin-4 PET detected up-regulated cardiac GLP-1R expression during the healing of MI in rats. The uptake of 68Ga-NODAGA-exendin-4 was also increased in inflamed atherosclerotic lesions in mice. In conclusion, PC immunotherapy might represent a potential approach to inhibit the lipid-driven inflammation in atherosclerosis. 68Ga-NODAGA-exendin-4 PET may have implications for studying pharmacological modification of GLP-1R signaling in ASCVD.

Molekyylikuvantaminen ja immunoterapia ateroskleroottisissa sydän-ja verisuonitaudeissa Sydän-ja verisuonitautien yleisin syy on ateroskleroosi, mikä on krooninen matala-asteinen tulehduksellinen sairaus, jossa rasvaa kertyy valtimoiden seinämiin. Muokkautuneiden rasvapartikkelien pinnalta on tunnistettu tulehdusreaktiota edistäviä molekyylejä kuten fosforyylikoliini, jotka ovat osallisena valtimoplakkien muodostumiseen. Suurimman osan sydäninfarkteista aiheuttaa epävakaan tulehtuneen ateroskleroottisen plakin repeytyminen sepelvaltimossa. Sydäninfarkti saa aikaan tulehdusreaktion ja arpikudoksen muodostumisen sydänlihaksessa, mikä pitkittyneenä voi johtaa myös sydämen vajaatoimintaan. Molekyylikuvantamisen avulla voisi olla mahdollista tunnistaa ja tutkia uusia kohteita kuten glukagonin kaltainen peptidi-1 (GLP-1) -reseptori, jotka liittyvät sydäninfarktinjälkeiseen tulehdusreaktioon ja arven paranemiseen. Tämän väitöskirjan tarkoituksena oli tutkia koe-eläinmalleissa, miten uusi fosforyylikoliini-molekyyliin kohdentuva immunoterapia vaikuttaa ateroskleroottisten suonten toimintaan ja tulehdukseen. Lisäksi tutkittiin GLP-1-reseptorin ilmentymistä sydäninfarktin jälkeen ja ateroskleroottisissa plakeissa 68Ga¬NODAGA-exendin-4 merkkiaineen ja positroniemissiotomografia (PET)-kuvantamisen avulla. Tutkimusmenetelminä käytettiin in vivo PET-ja ultraäänikuvantamista, autoradiografiaa, kudosvärjäyksiä ja solukokeita. Väitöskirjassa havaittiin, että fosforyylikoliini-immunoterapian jälkeen hiirten sepelvaltimoiden toiminta oli parantunut ja plakkeihin kertyi vähemmän 18F-FDG¬merkkiainetta, mikä kertoo laantuneesta tulehduksesta. 68Ga-NODAGA-exendin-4 PET-kuvantaminen osoitti, että GLP-1-reseptorin ilmentyminen oli lisääntynyt infarktinjälkeisen tulehdusreaktion aikana. 68Ga-NODAGA-exendin-4-merkkiaine kertyi myös selvästi tulehtuneisiin ateroskleroottisiin plakkeihin. Yhteenvetona voidaan todeta, että fosforyylikoliini-immunoterapia saattaisi olla potentiaalinen uusi lääkehoito valtimoplakkien tulehdusreaktion hillitsemiseksi. 68Ga-NODAGA¬exendin-4 PET-kuvantamista voitaisiin hyödyntää GLP-1-reseptoriin kohdentuvien lääkehoitojen tutkimisessa ateroskleroottisissa sydän- ja verisuonitaudeissa.